Persons with Disabilities in the Public Library "Stefan Prvovenčani", Kraljevo. Examples of good practices and challenges - Gvozdenović, Ana (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
The paper consists of three parts. In the first, the author considers statistics from the last census in Serbia (2011) which clarify the number, structure and social and economic position of people with disabilities in the Serbian population. In the second part, the author reminds us of international law and human obligations with regard to persons with disabillities, and in the third, she brings the examplesof good practice in ?Stefan Prvovenčani? Public Library in Kraljevo, with regard to persons with disabillities as users of librarian services as well as employees and human resources.
Keywords: Biblioteka Publiczna Stefana Prvovenčani w Kraljevie; osoby z niepełnosprawnością; użytkownicy bibliotek; pracownicy bibliotek; Stefan's Prvovenčani Public Library in Kraljevo; people with disabilities; library users; library workers